If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + 3 = -4 Reorder the terms: 3 + 3n = -4 Solving 3 + 3n = -4 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 3n = -4 + -3 Combine like terms: 3 + -3 = 0 0 + 3n = -4 + -3 3n = -4 + -3 Combine like terms: -4 + -3 = -7 3n = -7 Divide each side by '3'. n = -2.333333333 Simplifying n = -2.333333333
| 123456789-987654321=0 | | (9-10)x= | | -6x^2+5x+6=7.01466 | | 1x+1-2-(3-x)=6-(1-1) | | (3x^2+3x-8)+(3x^2+6x+17)-(6x^2-17)= | | 17-x=33(x+7) | | 6-2(3x-4)=12 | | (3x^2+3x-8)+(3x^2+6x+17)-(6x^2-17)= | | A=2x+2y | | 3t+4=16 | | (3x^2+3x-8)+(3x^2+6x+17)-(6x^2-17)= | | A=2x+2y | | -6x^2+5x+6=1.41666 | | -3+6x=5x-13 | | 8y-9=2-88yip | | 6/5x-8=3/4x | | 27+2x+5+3x-4=180 | | (3x^2+3x-8)+(3x^2+6x+17)-(6x^2-17)= | | ax^2+5x+6=1.41666 | | 6/5x-8=3/4x | | 6/5x-8=3/4x | | -3+6x=5x-13 | | -3+6x=5x-13 | | 9(x-8)+28=9x-44 | | 6/7*7/8 | | 27+2x+5+3x-4=180 | | -9(9+u)-2u=-10 | | 3t+4+t=6 | | (3t^4)(-2t)(5t^6)=x | | -9(9+u)-2u=-10 | | -3+6x=5x-13 | | 6/7*7/8 |